PENGARUH PENERIMAAN DANA ZISWAF, BOPO, LABA/RUGI NON-OPERASIONAL DAN FIRM SIZE TERHADAP GIRO WAJIB MINIMUM (GWM) PADA PERBANKAN SYARIAH PERIODE 2018.Q1-2023.Q3 - hanifaturasyda, arfina; Eka Wahyu Hestya Budianto (Universitas Tulungagung, 2024)
Abstract The intention of this analysis is to establish the impact of ZISWAF Fund Receipts, BOPO, and Non-Operational Profit/Loss on GWM in Sharia Banking in Indonesia, while considering Firm Size as a moderating factor. The research utilizes secondary data sourced from annual reports obtained through ojk.go.id and websites belonging to associated companies. The sampling method employed was selective sampling. With total of 5 financial reports from islamic banking companies for the period of 2018.Q1-2023.Q3 were utilized as the sample. Determined from the research findings, it is apparent that there is infinitesimal impact on the Statutory Reserve from receiving ZISWAF, BOPO, and non-operational profit/loss funds. Moreover, when considering moderating variables, it is observed that firm size does not have the capacity to moderate the effects of receiving ZISWAF funds, BOPO, and non-operational profit/loss on the Minimum statutory Reserve in Islamic banking in Indonesia from 2018.Q1 to 2023.Q3. In future research, it is hoped that other variables will be used as moderating variables. Apart from that, it is better not only to look at the banking sector, but also to look at companies from the other sectors. Abstrak Dengan menggunakan ukuran perusahaan sebagai faktor moderasi, analisis ini bertujuan untuk mengetahui bagaimana GWM pada perbankan syariah di Indonesia dipengaruhi oleh penerimaan dana ZISWAF, BOPO, dan laba/rugi non-operasi. Analisis didasarkan pada data sekunder yang diperoleh dari laporan tahunan OJK.go.id dan website perusahaan terkait. Jumlah lima laporan keuangan Perbankan Syariah diambil sampel melalui metode sampel pilihan. Hasil penelitian menunjukkan bahwa penerimaan dana ZISWAF, BOPO, dan laba/rugi non-operasi tidak memengaruhi Giro Wajib Minimum secara signifikan. Selanjutnya, pada interaksi variable moderasi, ukuran perusahaan tidak dapat memoderasi penerimaan dana ZISWAF, BOPO, dan laba/rugi non-operasi terhadap GWM pada perbankan syariah di Indonesia dari 2018 Q1 hingga 2023 Q3. Terdapat harapan bahwa variabel tambahan akan digunakan sebagai variabel moderasi dalam penelitian mendatang. Disarankan untuk melihat perusahaan dari berbagai bidang selain industri perbankan.